Prevalence of adverse cardiometabolic health markers in UK undergraduate university students: an observational cohort study - Daniele Magistro; Matthew J Savage; Ruth M James; Alfie G Price; Eleanor L Procter; Philip Hennis (BMJ Open)
Objectives The prevalence of adverse cardiometabolic health markers has increased substantially in UK young adults, and university students now make up a significant proportion of this population. Their health-related behaviours are poorer than age-matched normative data, and students’ anthropometric outcomes deteriorate during their university career. The influence of university on cardiometabolic health markers is unclear, and men and students of Minoritised Ethnicity are often under-represented in student health research. This study aimed to determine the prevalence of adverse cardiometabolic health markers in undergraduate university students and assess differences between genders, ethnic groups and year of study.Design Observational cohort study.Setting A higher education institution in Nottingham, UK.Participants Three independent cohorts of undergraduate university students (total n=1,299) completed five physiological tests and provided demographic information. One-way ANOVAs assessed differences between year of study and ethnic groups, and paired samples t-tests assessed differences between genders.Main outcome measures Body mass index (BMI), waist circumference, waist to hip ratio (WHR), waist to height ratio (WHtR), blood pressure (BP) and glycated haemoglobin concentrations (HbA1c).Results 34.5% had overweight or obesity, 7.6% had a ‘very high’ waist circumference, 11.0% had a high WHR, 25.5% had a high WHtR, 12.7% were classified as hypertensive and 3.0% had an HbA1c ≥42 mmol/mol, indicating impaired glucose regulation. Differences between year groups were present for diastolic BP and HbA1c (p<0.01). Gender and ethnic group differences (p<0.05) were present for all variables other than BMI (gender) and diastolic BP (gender and ethnic group).Conclusion Overall, these data demonstrate the prevalence of adverse cardiometabolic health markers in UK undergraduate university students, highlighting differences between year groups, genders and ethnic groups. These findings should be considered when developing strategies to promote healthy lifestyles in higher education.